Space Program Scheme for 3-D NAND Flash Memory Specialized for the TLC Design - Kang, Ho-Jung; Choi, Nagyong; Lee, Dong Hwan; Lee, Tackhwi; Chung, Sungyong; Bae, Jong-Ho; Park, Byung-Gook; Lee, Jong-Ho (2018 IEEE Symposium on VLSI Technology, 2018)
A new space program (PGM) scheme is proposed to achieve reliable triple-level-cell (TLC) 3-D NAND flash memory. Considering the lateral diffusion issue of stored electrons in the nitride storage layer, the proposed scheme stores electrons in the nitride layer of the space region between adjacent cells to suppress the lateral movement of trapped electrons in the programmed target cells. The effect of the space PGM can be sustained until 10 4 s at 90 °C and up to 1k read cycles at 25 °C. The programmed space region of the nitride layer improves the retention characteristics of the cells in the PGM state by 40% and remarkably reduces the V th redistribution.